Pengaruh Persekitaran Luaran ke atas Prestasi Perniagaan PKS (Sains Humanika, 2018)
This paper examines the influence of the external environment on business performance of SMEs in Malaysia. Previous studies have show that there was inconsistent relationship between external environment variables and business performance. Three external environment variables were examined in this study namely dynamic, hostility and munifience. By using simple random sampling technique, a total of 143 SMEs in Malaysia were used as samples in this study. Correlation analysis and multiple regression were used to test the three hypothesis. Results of the analysis showed that the three independent variables, i.e., dynamic, hostility and munifience have positive significant relationships with business performance. It is hoped that the findings from this study can be utilized by the government, entrepreneurs, researchers and other stakeholders in the field of SMEs in Malaysia.
Keywords: Business performance; external environment; Small and Medium Enterprises (SMEs)